The conservation of Madagascar’s orchids . A model for an integrated conservation project - Cribb, Phillip; Hermans, Johan (Lankesteriana: International Journal on Orchidology, 2015)
The fauna and flora of the large island of Madagascar, situated in the eastern Indian Ocean off the coast of East Africa, has been recognised for many years as one of the most peculiar anywhere in the world, and as one of the most endangered. It has a rich orchid flora of about 1000 species.